Abdominal cocoon syndrome: diagnostic challenge in an uncommon entity - Dave, Katha H.; Saraf, Nidhi A.; Dalal, Archana D.; Suthar, Kalpit R.; Vagela, Sagar J. (International Surgery Journal, 2025)
Abdominal cocoon syndrome (ACS) also known as sclerosing encapsulating peritonitis (SEP) is a rare condition where thickened fibro-collagenous peritoneal membrane encases parts of the small intestine likely due to recurrent inflammatory processes. Aetiology is unidentified in most of the cases but it is notably associated with patients on chronic peritoneal dialysis for end stage renal disease. Diagnosis is usually intraoperative. However, CECT abdomen is a definitive radiological imaging modality of choice. SEP can be managed both conservatively as well as surgically. Here, we present a case of 48-year-old female patient presenting with features of small bowel obstruction and sepsis and was a known case of chronic liver disease (CLD). She had history of episodes of recurrent small bowel obstruction. She was managed conservatively for the same. She was diagnosed with the help of CECT abdomen and was managed conservatively in view of high-risk surgery due to poor general health and comorbid conditions. She could not survive and succumbed to liver dysfunction and sepsis.